Processus de formation des expressions figées kabyles : cas de la polysémie - Mahdi Yahiaoui (Multilinguales)
This study aims to demonstrate the process of formation of static Kabyle expressions. This work is essentially based on the role of polysemic units in the formation of fixed expressions. The first part is devoted to the census of the sememes to reconstitute the process of formation of the fixed sense. The second part is devoted to determining the role of polysemic units and how they orient meaning within expressions.